Genotypes of SLC22A4 and SLC22A5 regulatory loci are predictive of the response of chronic myeloid leukemia patients to imatinib treatment - Jaruskova, Monika; Curik, Nikola; Hercog, Rajna; Polivkova, Vaclava; Motlova, Eliska; Benes, Vladimir; Klamova, Hana; Pecherkova, Pavla; Belohlavkova, Petra; Vrbacky, Filip; Machova Polakova, Katerina (Journal of experimental & clinical cancer research, 2017)
BACKGROUND: Through high-throughput next-generation sequencing of promoters of solute carrier and ATP-binding cassette genes, which encode drug transporters, we aimed to identify SNPs associated with the response to imatinib administered for first-line treatment of patients with chronic myeloid leukemia. METHODS: In silico analysis using publicly available databases was done to select the SLC and ABC genes and their promoters for the next-generation sequencing. SNPs associated with the imatinib response were identified using Fisher's exact probability tests and subjected to the linkage disequilibrium analyses with regulatory loci of concerned genes. We analyzed cumulative achievement of major molecular response and probability of event free survival in relation to identified SNP genotypes in 129 CML patients and performed multivariate analysis for determination of genotypes as independent predictors of outcome. Gene expression analysis of eight cell lines naturally carrying different genotypes was performed to outline an impact of genotypes on the gene expression. RESULTS: We observed significant differences in the frequencies of the rs460089-GC and rs460089-GG (SLC22A4) genotypes among rs2631365-TC (SLC22A5) genotype carriers that were associated with optimal and non-optimal responses, respectively. Loci rs460089 and rs2631365 were in highly significant linkage disequilibrium with 12 regulatory loci in introns of SLC22A4 and SLC22A5 encoding imatinib transporters. Genotype association analysis with the response to imatinib indicated that rs460089-GC carriers had a significantly higher probability of achieving a stable major molecular response (BCR-ABL1 transcript level below or equal to 0.1% in the international scale). In contrast, the rs460089-GG represented a risk factor for imatinib failure, which was significantly higher in rs460089-GG_rs2631365-TC carriers. CONCLUSIONS: This exploratory study depicted potentially important genetic markers predicting outcome of imatinib treatment, which may be helpful for tailoring therapy in clinical practice.
Keywords: Solute Carrier Family 22 Member 5; Mutation Rate; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Humans; Promoter Regions, Genetic; imatinib mesylát; mutační rychlost; Sequence Analysis, DNA; Organic Cation Transport Proteins; Response; Imatinib Mesylate; jednonukleotidový polymorfismus; Female; buňky K562; proteiny přenášející organické kationty; Antineoplastic Agents; výsledek terapie; Genotype; lidé; CML; sekvenční analýza DNA; Imatinib; ženské pohlaví; K562 Cells; Male; chronická myeloidní leukemie; symportéry; vazebná nerovnováha; Treatment Outcome; vysoce účinné nukleotidové sekvenování; nádorové buněčné linie; protinádorové látky; SLC; High-Throughput Nucleotide Sequencing; genotyp; Cell Line, Tumor; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; mužské pohlaví; Symporters; rodina nosičů rozpuštěných látek 22, člen 5; promotorové oblasti (genetika)